Age-related Neural Reorganization during Spoken Word Recognition: The Interaction of Form and Meaning - Shafto, Meredith (2012)
Research on language and aging typically shows that language comprehension is preserved across the life span. Recent neuroimaging results suggest that this good performance is underpinned by age-related neural reorganization [e.g., Tyler, L. K., Shafto, M. A., Randall, B., Wright, P., Marslen-Wilson, W. D., & Stamatakis, E. A. Preserving syntactic processing across the adult life span: The modulation of the frontotemporal language system in the context of age-related atrophy. Cerebral Cortex, 20, 352–364, 2010]. The current study examines how age-related reorganization affects the balance between component linguistic processes by manipulating semantic and phonological factors during spoken word recognition in younger and older adults. Participants in an fMRI study performed an auditory lexical decision task where words varied in their phonological and semantic properties as measured by degree of phonological competition and imageability. Older adults had a preserved lexicality effect, but compared with younger people, their behavioral sensitivity to phonological competition was reduced, as was competition-related activity in left inferior frontal gyrus. This was accompanied by increases in behavioral sensitivity to imageability and imageability-related activity in left middle temporal gyrus. These results support previous findings that neural compensation underpins preserved comprehension in aging and demonstrate that neural reorganization can affect the balance between semantic and phonological processing.